Assessing the effects of the COVID-19 pandemic on new ART initiation and viral load access among children and adolescents living with HIV in West Africa: an interrupted time series analysis - Konu, Yao Rodion; Malateste, Karen; Desmonde, Sophie; Dahourou, Désiré; Amorissani-Folquet, Madeleine; Sylla, Mariam; Yonaba, Caroline; Tossa-Bagnan, Lehila; Dame, Joycelyn; Ekouevi, Didier Koumavi; Leroy, Valériane (Frontiers in Public Health, 2025)
BackgroundBefore the COVID-19 pandemic, the pediatric continuum of HIV care lagged behind that of adults. The present study aimed to describe the effects of the COVID-19 pandemic on access to HIV care among children and adolescents (0–19 years) living with HIV (CALHIV) in five West African countries.MethodsWithin this observational multicenter study, we conducted an interrupted time series analysis by including all antiretroviral therapy (ART)-naive CALHIV newly enrolled between 2018 and 2021. Two monthly documented outcomes were analyzed, namely, the number of ART initiators and the number of viral load (VL) tests performed. We fitted Poisson segmented regression models to estimate immediate changes at pandemic onset and per-pandemic trends through incidence rate ratios (IRRs) with 95% confidence intervals (CIs).ResultsImmediately after the start of the pandemic, the average number of ART initiations decreased by 83.8% in Burkina Faso (IRR: 0.162; [95%CI: 0.043–0.609]) and 70.9% in Ghana (IRR: 0.291 [0.171–0.494]). Similarly, the number of VL tests performed decreased by 51% in Burkina Faso (IRR: 0.409 [0.253–0.662]). There were no significant trends in the number of ART initiations during the pandemic, except in Ghana (IRR: 1.146 [1.073–1.224]). The number of VL tests performed monthly in clinics in Côte d’Ivoire and Ghana decreased during the pandemic.ConclusionART initiation and VL testing activities were maintained in the majority of West African pediatric clinics, despite the COVID-19 pandemic and subsequent crisis. HIV care continuum monitoring in CALHIV should be maintained during the postpandemic period to identify and mitigate potential lasting effects.